The U.S. Naval Institute on naval tactics - Hughes, Wayne P., 1930- (U.S. Naval Institute wheel books, 2015)
"Wheel books" were once found in the uniform pockets of virtually all junior officers and many senior petty officers. Each small notebook was unique to the Sailor carrying it, but all had in common a collection of data and wisdom that the individual deemed useful in the effective execution of his or her duties. Often used as a substitute for experience among neophytes and as a portable library of reference information for more experienced personnel, those weathered pages contained everything from the time of the next tide, to leadership hints from a respected chief petty officer, to the color.